EKSPLORASI PEMANFAATAN SENI TRADISIONAL PADA DESA-DESA WISATA DI KABUPATEN SLEMAN - Enis Niken Herawati (Imaji, 2012)
The main purpose of this study is to assess the cultural arts in some villages in Sleman district. In particular, this study aims to: 1) describe the types of traditional arts in tourist villages in Sleman district, 2) describe the presentation of traditional art performed in every tourism village in Sleman district, 3) describe the efforts to preserve the kinds of traditional art which are likely developed in the tourist villages in Sleman district. The results reveal that in some developing tourist villages there are many traditional art forms such as dance, traditional music (gamelan), puppet art, traditional games for children, with their own kind of variety. Art traditions in rural tourism are presented in a simple way and yet touched with good aesthetic arts that are still hereditary. The presentation of a certain kind of art attractions is based on the demand of visitors, but some are conducted based on the initiative coming from the tourist village manager. The traditional art in the main tourist village is used to attract visitors to come. It is also used as a venue for traditional art reception, entertainment, cultural recognition, the regeneration of art activists, and community empowerment.